Shaw on Music - Shaw, Bernard 1856-1950; Bentley, Eric (New York Applause, 1995)
This volume contains the best of Shaw's musical writing, including sections on Gluck, Handel, Mozart, Beethoven, Rossini, Verdi, Berlioz, pieces on opera, musical analysis, oratorios, Gilbert and Sullivan, plus a long autobiographical preface, one of Shaw's most self-revealing works. The result is a book of unparalleled brilliance and grace by a writer who, according to W.H. Auden, "was probably the greatest music critic who ever lived." "For all music collections." - Library Journal
Keywords: 19th Century (1801-1900); 20th Century (1901-2000); Music criticism; United Kingdom